Balance of Payment Statistics Yearbook 2017. (Balance of Payments Statistics; Balance of Payments Statistics ;, 2017)
This paper analyses that the IMF has published data on a basis that is consistent across countries and across time periods. Such data consistency is required to perform cross-country data comparisons, track growth rates across time, and produce regional or global data aggregates. The methodologies, compiling practices, and data sources available through data.imf.org and DVD-ROM are based on information provided to the IMF by reporting countries. The descriptions are intended to enhance user understanding of the coverage, as well as the limitations, of individual country data. The estimation procedure is based largely on the use of the WEO database in BPM6 format. For a variety of reasons, however, countries may not correctly record some transactions, or they classify corresponding transactions differently. Under these circumstances, errors and omissions in the national data and asymmetries (discrepancies) in the global statistics arise.